Phosphoryl-Graphene for High-Efficiency Uranium Separation and Recycling - Pykal, Martin; Šedajová, Veronika; Thakur, Aditya; Sengupta, Somnath; Brahmananda Rao, Cherukuri Venkata Siva; Zbořil, Radek; Sreenivasulu, Balija; Otyepka, Michal; Jayaramulu, Kolleboyina (ACS applied materials & interfaces, 2025)
To enhance the sustainability of nuclear energy and protect the environment, the efficient extraction of uranium from various water sources has emerged as an essential strategy for addressing the long-term challenges of nuclear waste management. In this study, we designed phosphoryl-functionalized graphene (PG) for efficient uranyl adsorption and synthesized the material from fluorinated graphene using phosphoryl ethanolamine under solvothermal conditions. The resultant PG features a unique 2D structure equipped with solvent-exposed phosphoryl groups, making it highly suitable for uranium adsorption in aqueous solutions. Notably, PG demonstrated a high sorption efficiency (∼77%) with rapid extraction capability (∼5 min) for U(VI) from aqueous media at pH 7, achieving an adsorption capacity of 316 mg U g-1. It also demonstrates good recyclability and stability even after 3 cycles and exhibits a significant seawater adsorption capacity of 117.8 mg U g-1. Both X-ray photoelectron spectroscopy analysis and molecular dynamics simulations revealed a preferential binding of uranyl ions to the phosphoryl groups of PG. This work paves the way for designing and developing functional graphene derivatives for efficient uranium extraction from various water resources, with promising potential for the recovery of other radioactive elements.
Keywords: molecular dynamics simulations; graphene derivatives; two-dimensional (2D) materials; phosphoryl-functionalized graphene; uranium adsorption